Early Seizure Freedom Is a Prognostic Factor for Survival in Patients with West Syndrome - Krijgh, E. J. C.; Catsman-Berrevoets, C. E.; Neuteboom, R. F. (Neuropediatrics, 2018)
Introduction West syndrome (WS) is a devastating epileptic encephalopathy with substantial mortality. After a study by Riikonen in 1996, further data on mortality and prognostic factors for survival has been scarce. We aimed to study mortality in patients with WS and identify prognostic factors for survival.Methods We performed a single-center retrospective study in a tertiary referral clinic (Erasmus University Hospital/Sophia Children's Hospital). This study obtained data from deceased patients regarding the age of death and cause of death. Seizure outcome was assessed at 8 weeks after the start of treatment and at 1 year after the onset of WS. At 1 year of follow-up seizure frequency, number of antiepileptic drugs and seizure type were evaluated.Results With a mean follow-up of 60 months (range 8–314 months), 162 patients met the inclusion criteria. At 8 weeks and 1 year of follow-up, 64 patients (40%) were seizure free. Overall, 37 patients (23%) died. The cumulative mortality percentage was 31%. Seizure freedom was an independent predictor of survival (p = 0.01).Conclusion In this study, remission of seizures at 8 weeks of follow-up was significantly associated with reduced mortality in patients with WS.
Keywords: prognostic factors; mortality; pediatric; seizure freedom; West syndrome